Surfing on a new wave of single-molecule fluorescence methods. - Hohlbein, J; Gryte, K; Heilemann, M; Kapanidis, A (2010)
Single-molecule fluorescence microscopy is currently one of the most popular methods in the single-molecule toolbox. In this review, we discuss recent advances in fluorescence instrumentation and assays: these methods are characterized by a substantial increase in complexity of the instrumentation or biological samples involved. Specifically, we describe new multi-laser and multi-colour fluorescence spectroscopy and imaging techniques, super-resolution microscopy imaging and the development of instruments that combine fluorescence detection with other single-molecule methods such as force spectroscopy. We also highlight two pivotal developments in basic and applied biosciences: the new information available from detection of single molecules in single biological cells and exciting developments in fluorescence-based single-molecule DNA sequencing.